Design of the FemCure study: prospective multicentre study on the transmission of genital and extra-genital Chlamydia trachomatis infections in women receiving routine care. Issue 1 (December 2016) - Dukers-Muijrers, Nicole; Wolffs, Petra; Eppings, Lisanne; Götz, Hannelore; Bruisten, Sylvia; Schim van der Loeff, Maarten; Janssen, Kevin; Lucchesi, Mayk; Heijman, Titia; van Benthem, Birgit; van Bergen, Jan; Morre, Servaas; et al.
Abstract Background In women, anorectal infections withChlamydia trachomatis (CT) are about as common as genital CT, yet the anorectal site remains largely untested in routine care. Anorectal CT frequently co-occurs with genital CT and may thus often be treated co-incidentally. Nevertheless, post-treatment detection of CT at both anatomic sites has been demonstrated. It is unknown whether anorectal CT may play a role in post-treatment transmission. This study, called FemCure, in women who receive routine treatment (either azithromycin or doxycycline) aims to understand the post-treatment transmission of anorectal CT infections, i.e., from their male sexual partner(s) and from and to the genital region of the same woman. The secondary objective is to evaluate other reasons for CT detection by nucleic acid amplification techniques (NAAT) such as treatment failure, in order to inform guidelines to optimize CT control. Methods A multicentre prospective cohort study (FemCure) is set up in which genital and/or anorectal CT positive women (n  = 400) will be recruited at three large Dutch STI clinics located in South Limburg, Amsterdam and Rotterdam. The women self-collect anorectal and vaginal swabs before treatment, and at the end of weeks 1, 2, 4, 6, 8, 10, and 12. Samples are tested for presence of CT-DNA (by NAAT), load (by quantitative polymerase chain reaction -PCR), viability (by culture and viability PCR) and CT type (by multilocus sequence typing). Sexual exposure is assessed by online self-administered questionnaires and by testing samples for Y chromosomal DNA. Using logistic regression models, the impact of two key factors (i.e., sexual exposure and alternate anatomic site of infection) on detection of anorectal and genital CT will be assessed. Discussion The FemCure study will provide insight in the role of anorectal chlamydia infection in maintaining the CT burden in the context of treatment, and it will provide practical recommendations to reduce avoidable transmission. Implications will improve care strategies that take account of anorectal CT. Trial registration ClinicalTrials.gov Identifier:NCT02694497 .